Educational and research activities of students: creating effective pedagogical conditions during the pandemic - A. M. Zhanburbayeva; E. K. Breitigam (Obrazovanie i Nauka)
Introduction. The rapidly growing pace of updating the content of education, informatisation and humanisation of the learning process are also changing the approaches to organising the educational activities of students. This problem became especially acute during the 2020 COVID-19 pandemic, when general education schools began to massively switch to distance learning.Aim. The research aims to analyse the effectiveness of the pedagogical conditions for the formation of educational and research activities of students in schools in Kazakhstan during the pandemic.Methodology and research methods. To achieve this goal, the authors conducted an experimental study, which involved 196 students and 20 teachers of secondary schools of the Altai district of the East Kazakhstan region of the Republic of Kazakhstan. The research methodological framework is based on the following approaches: personality-oriented and activity-based (B .G. Ananiev, L. S. Vygotsky, S. L. Rubinshtein), systemic (V. G. Afanasiev, V. N. Sadovsky, E. G. Yudin) and axiological (K. A. Abulkhanova, A. G. Asmolov, A. A. Derkach). The leading theoretical research methods were the analysis of psychological and pedagogical literature, advanced pedagogical experience, dissertations and scientific research. The main empirical research methods were a pedagogical experiment, survey and observation. Diagnostic and statistical methods were used to evaluate the results of the study.Results. The pedagogical conditions for the formation of educational and research activities of students are determined (complex use of methods for solving educational and research problems; creation of problem situations; application of the project method; use of means for the development of critical thinking (special questions, situation analysis, reflective essay); organisation of students’ activities at the lesson in the following order: joint activity → independent activity and independent activity → joint activity, organisation of special intellectual games, study of special courses). Motivational, cognitive, activity and personal components of educational and research activities were identified. The authors presented the analysis of the results of the experimental study (the increase in the level of development of motivational, cognitive, activity and personal components of educational and research activities). The criteria for evaluating the effectiveness of the process of formation of educational and research activities of students were formulated. The criteria for evaluating the motivational component were determined as the leading motives of learning: from external and social to cognitive motives. The criteria for evaluating the cognitive component determined students’ understanding of the text of the educational and research task, as well as understanding the issue, the correct and rational way of solving it. The criteria for evaluating the activity component were the skills and abilities of students acquired as a result of educational and research activities. The criteria for assessing the development of the personal component determined the ratio of the levels of self-regulation, self-organisation, self-education and self-development of students.Scientific novelty. The pedagogical conditions for the formation of educational and research activities have been identified, theoretically substantiated, and their effectiveness during the pandemic period has been proven.Practical significance. The research results are interdisciplinary in nature and can be used to organise the learning process among students in grades 5–11 of general education schools, as well as to improve teacher methodology training.